PENCATATAN LAPORAN KEUANGAN PADA UMKM DI KECAMATAN MEDAN TEMBUNG - Henny Andriyani Wirananda; Alistraja D Silalahi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
Accounting is an information system that is used to convert data from transactions into financial information. At first, accounting was only in the form of records of anything that happened in the activities of a business, then accounting records developed into double-entry, namely recording with the debit side and the credit side. Accounting is used as a standard to facilitate UMKM in making financial reports that can be accounted for and understood by external and internal parties. Accounting practices should have been widely known or even practiced by UMKM. The purpose of this study is to find out and analyze what accounting practices are like at UMKM in Medan Tembung District. This research is a qualitative research with data collection in the form of observations, interviews and questionnaires on UMKM in the District of Medan Tembung. The population in this study was 100 populations representing UMKM in the Medan Tembung sub-district. The results of the study found that the financial statements of UMKM were still simple by recording transactions that often occurred in their business and SAK was still not understood by UMKM owner. One of the factors that affect this is because of the lack of educational background and socialization or training from the government and institutions that oversee UMKM are still not optimal so that the understanding of the importance of financial reports is still not understood by UMKM owner.